A Review of automotive green technology: Potential of butanol as biofuel in gasoline engine - Sri Mumpuni Ngesti Rahayu; April Lia Hananto; Safarudin Gazali Herawan; Ahmed Sule; Muhammad Idris; Dhany Hermansyah; Shuaibu Alani Balogun; Esam Abu Baker Ali; Muhammad Zacky Asy'ari (Mechanical Engineering for Society and Industry, 2022)
In comparison to ethanol biofuel, butanol is considerably less corrosive, permitting the utilization of existing infrastructures used to ship gasoline or diesel for its distribution. Less corrosive also means that butanol can be utilized with no engine alteration. If butanol is mixed with water, it is less likely to split from the main fuel, thus facilitating the storage and distribution of blended fuels. Butanol also comprises a comparable energy content to petrol fuel, with 25% more energy density/liter as opposed to ethanol. All these excellent qualities have led to higher engine performance, enabling the vehicles to achieve higher mileage using butanol with no significant issue. Several challenges and future research directions are discussed and in the last section of this review article, we emphasize the importance of an optical engine to diagnose engine combustion in more detail. The consequence of using butanol on spark ignition engine on cold start and knock phenomena are also worth investigating. Results on the spray, the pressure inside the cylinder, rate of heat release, and detonation are thus required.